1989
DOI: 10.1111/j.1752-1688.1989.tb03084.x
|View full text |Cite
|
Sign up to set email alerts
|

UNCERTAINTY ANALYSIS OF RUNOFF ESTIMATES FROM A RUNOFF CONTOUR MAP1

Abstract: The U.S. Environmental Protection Agency (EPA) in cooperation with the U.S. Geological Survey (USGS) conducted an analysis to quantify the uncertainty associated with interpolating runoff to specific sites using a runoff contour map. We interpolated runoff to 93 gaged watersheds from a runoff contour map using (1) hand interpolation to the watershed outlet, (2) a computer interpolation to the watershed outlet, and (3) hand interpolation to the watershed centroid. We compared the interpolated values to the actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 5 publications
3
33
0
Order By: Relevance
“…Interpolation was also used by Gebert et al (1987), when they developed a spatially complete flow map of the US. Rochelle et al (1989) have also concluded that interpolation from a total flow contour map provides adequate estimates for un-gauged systems and recommended using total flow contour maps for environmental issues at regional scale.…”
Section: Estimation Of Base Flow Volume For the Conterminous United Smentioning
confidence: 96%
See 1 more Smart Citation
“…Interpolation was also used by Gebert et al (1987), when they developed a spatially complete flow map of the US. Rochelle et al (1989) have also concluded that interpolation from a total flow contour map provides adequate estimates for un-gauged systems and recommended using total flow contour maps for environmental issues at regional scale.…”
Section: Estimation Of Base Flow Volume For the Conterminous United Smentioning
confidence: 96%
“…Base flow volume was then estimated by multiplying total flow volume map with digital filter base flow index map. For the total flow interpolation, a study by Rochelle et al (1989) on the uncertainty analysis of total flow estimates from the flow contour map has shown that uncertainty could be about 15% due to interpolation. Interpolation was also used by Gebert et al (1987), when they developed a spatially complete flow map of the US.…”
Section: Estimation Of Base Flow Volume For the Conterminous United Smentioning
confidence: 98%
“…As researchers gained access to higher-powered computers, efforts were made to automate the development of maps of mean annual runoff (Langbein and Slack, 1982). In both Europe and the United States, maps of mean annual runoff generated by geostatistical techniques were found to be as accurate as their hand-drawn predecessors (Rochelle et al, 1989;Domokos and Sass, 1990;Church, 1992, 1995). Mapping techniques have also been used to explore other streamflow statistics (Gottschalk et al, 2006;Archfield et al, 2013) and to assess the accuracy and performance of hydrologic models (Sauquet and Leblois, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the accuracy of the various runoff maps, we conducted a quantitative uncertainty analysis employing the techniques and data used by Rochelle et al (1989) and Bishop and Church (1995) in their analysis of runoff estimates made from long-term average runoff contour maps. The analysis consisted of estimating runoff by interpolation from the maps to the watershed centroids of a set of gage sites withheld from the creation of the maps to be tested and then comparing the interpolated and actual values.…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…Our goal was to determine what, if any, improvements in accuracy could be derived from using the 5-km resolution estimates. We use two of the evaluation techniques employed by Rochelle et al (1989), and Bishop andChurch (1992, 1995) in similar studies: visual comparison and a quantitative uncertainty analysis using gaged sites withheld from the creation of any of the maps examined. Long-Term (1951-1980 Runoff for the Part of the Eastern United States Examined in this Study (source: Krug et al, 1990).…”
Section: Introductionmentioning
confidence: 99%